不同离子对核桃蛋白结构及功能特性的影响Effects of different ions on the structure and functionality of walnut protein - 任祥瑞1， 赵晓燕1， 刘红开1， 张晓伟1, 王萌1， 虎海防2"REN Xiangrui1, ZHAO Xiaoyan1, LIU Hongkai1, ZHANG Xiaowei1, WANG Meng1, HU Haifang2" (Zhongguo youzhi)
为了有效提高核桃蛋白的利用率，拓展核桃蛋白在食品领域的应用范围，采用阴离子（Cl-、PO3-4、S2O2-3、HCO-3）和阳离子（Na+、K+、Mg2+、Ca2+）对核桃蛋白进行改性，并对改性后核桃蛋白的结构与功能特性进行研究。结果显示：阴离子PO3-4、HCO-3 和阳离子Na+、Mg2+增加了核桃蛋白的巯基含量；除了Cl-和K+，其他6种离子改性核桃蛋白的二硫键含量均下降，其中HCO-3改性核桃蛋白下降最多；8种离子对核桃蛋白的亚基组成无影响；Cl-、PO3-4、Na+和Ca2+使核桃蛋白构象稳定性提高，而HCO-3会使核桃蛋白紧密程度变差；不同离子对核桃蛋白溶解度的影响存在差异；不同离子改性均提高了核桃蛋白的乳化性和乳化稳定性，其中阴离子PO3-4改性核桃蛋白的乳化性提高了2.52倍，而阳离子Na+改性核桃蛋白的乳化稳定性提高了46.22百分点；阴离子S2O2-3与阳离子Mg2+对核桃蛋白的起泡性影响最大，而Na+改性核桃蛋白的起泡稳定性最好；PO3-4改性核桃蛋白的持水性和吸油性均最高。综合来讲，Na+和Mg2+改性核桃蛋白的乳化性、乳化稳定性、起泡性和起泡稳定性相对更好。 In order to effectively improve the utilization rate of walnut protein and expand its application range in the field of food, walnut protein was modified by anions ( Cl-, PO3-4, S2O2-3, HCO-3) and cations ( Na+, K+, Mg2+, Ca2+ ), and the structure and functionality of the modified walnut protein were studied. The results showed that the anions PO3-4, HCO-3 and cations Na+, Mg2+ could increase the sulfhydryl content of walnut protein. Except Cl- and K+, the content of disulfide bonds in walnut protein treated with other six ions decreased, among which HCO-3 treated samples decreased the most. Eight ions had no effect on the subunit composition of walnut protein. The Cl-， PO3-4, Na+ and Ca2+ improved the stability of walnut protein conformation, while HCO-3 made the tightness of walnut protein worse. The effects of different ions on the solubility of walnut protein were different. The ions improved the emulsifying property and emulsion stability of walnut protein. The emulsifying property of walnut protein treated with anion PO3-4 increased 2.52 fold, while the emulsion stability of walnut protein treated with cation Na+ increased by 46.22 percentage points. The anion S2O2-3 and cation Mg2+ had the greatest effect on the foaming property of walnut protein, while the foam stability of walnut protein treated with Na+ was the best. The walnut protein treated with PO3-4 had the highest water holding capacity and oil absorption capacity. In general, the emulsifying property, emulsion stability, foaming property and foam stability of walnut protein treated with Na+ and Mg2+ are relatively better.